Parental Support in Developing the Love and the Use for the Filipino Language - Cutillas, Anesito L.; Rellin, Evangeline C.; Caynila, Rhea Jane L.; Pangandoyon, Ma Judiana S.; Sales, April Jane G. (Forum for Linguistic Studies, 2025)
This research explores the significant role of parental support in nurturing a love for and consistent use of the Filipino language among children. Employing a qualitative exploratory design, the study analyzed data collected through semi-structured interviews with 25 Filipino parents intentionally chosen for their active promotion of the Filipino language at home. The findings reveal a diverse range of strategies that parents employ to create a Filipino-speaking environment, including establishing “Filipino-only” days, incorporating the language into daily routines, and integrating Filipino media and cultural activities into family life. The study further emphasized the importance of emotional support and positive reinforcement in fostering a positive and nurturing environment for children to learn and practice Filipino. By praising efforts, using terms of endearment, and engaging children in interactive activities like cooking and celebrating cultural traditions, parents help children develop a strong sense of pride and ownership over the language. However, the research also acknowledges the challenges posed by globalization and the widespread use of English. The study concludes by emphasizing the significant contributions of parents in shaping children’s linguistic preferences and habits, ultimately promoting the preservation of the Filipino language as an essential component of their cultural identity.